(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The article describes the meaning of the concept of “competence”, as well as its analysis in the methodology of language teaching, and the approaches presented in research regarding the structures of linguistic competence. Based on the analysis, the definition of linguistic competence and the main stages of formation of linguistic competence in the process of teaching the mother tongue are discussed. The essence of using information and communication technologies for the more effective organization of the process of formation of linguistic competence and technologicalization of the process is also highlighted.